EVALUATION OF LAND SUITABILITY FOR PLANTATION CROPS AND MEDICINAL PLANTS IN THE INTERCROPPING SYSTEM IN CIOMAS DISTRICT, SERANG REGENCY - Putra Utama; Hermita Hermita; Diana Putri Angelina (AGRIBUSINESS JOURNAL, 2022)
The research was aimed to determine land suitability classes, limiting factors, and efforts to improve land suitability of plantation crops and medicinal plants in the intercropping system in Ciomas subdistrict Serang District. This type of research was descriptive. This research was carried out in Cisitu Village Ciomas Subdistrict Serang District and the soil laboratory of the Faculty of Agriculture Untirta from October 2018 until September 2019. The implementation of the study consisted of 5 stages: collecting data and information, determining soil sample points and field surveys, taking soil samples and field observations, laboratory analysis, data analysis and assessing land suitability classes. The method of data analysis was carried out with a matching system between the characteristics of the land in the study area with conditions for growing of plantation crops and medicinal plants. The results showed that the actual land suitability class for melinjo, clove, and turmeric plants was quite suitable (S2) with limiting factors for erosion hazard, and nutrient retention. Potential land suitability classes for melinjo, clove and turmeric are very suitable (S1). While the actual land suitability class of ginger plants was not suitable (N) with the limiting factor of water availability, the limiting factor cannot be improved. Improvement efforts that can be done to improve the limiting factors were by making terraces, providing organic material, and liming. The cropping pattern of intercropping that can be done was intercropping melinjo plants with turmeric plants and intercropping clove plants with turmeric plants.